The Use of Personification and Simile in Gibran’s The Broken Wings - Fadillah, Ridha (English Department of Faculty of Tarbiyah and Teacher Training, 2025)
This study is intended to analyze the language style of Gibran’s The Broken Wings by tracing the novel’s content and to discuss the meaning of Gibran’s clauses or sentences written in personification and simile. In this article, the writer discusses the elements of the novel generally. The method used is descriptive-qualitative. And the finding of the study is that the author’s way of using personification and simile is very much influenced by environment. Analysis reveals that Gibran’s use of figurative language, particularly personification and simile, serves to evoke emotional responses and reflect the social and spiritual conditions of his time. Through personification, nature and abstract concepts are given human traits, creating a deeper emotional resonance. The findings suggest that Gibran’s literary style is deeply rooted in his cultural background, personal experiences, and philosophical beliefs.